Menerapkan Prinsip-Prinsip Islam dalam Manajemen Konflik di Lembaga Pendidikan - Sintia Rosyidah; Lu’lu’ul Muhimah Nabilatul Maulidiyyah; Septa Tria Dinar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The application of Islamic principles in conflict management in educational institutions is very important to create a harmonious and productive environment. Conflicts that arise in educational institutions can be caused by various factors, both between students, teachers and between management. In Islam, there are several principles that can be applied to manage conflict in a fair and wise manner, including tabayun, deliberation, tahkim, and islah. Tabayun focuses on clarifying information so that conflict does not develop due to misunderstandings. Deliberation encourages collective decision making to reach solutions that benefit all parties. Tahkim involves a neutral third party to help resolve the conflict, ensuring justice for all parties involved. Meanwhile, islah emphasizes peace and reconciliation, with the aim of ending conflicts peacefully and restoring damaged relations. The application of these principles can increase understanding and skills in managing conflict, both among students, teachers and administrators of educational institutions. Thus, Islamic-based conflict management not only solves problems, but also creates a more just, peaceful environment and supports optimal student development.